Current State and Trends of Pedagogical Activity Development - Marchuk, L. S. (Харківська обласна громадська організація "Культура здоров'я", 2019)
Particularly relevant today are the problems connected with the restoration of the scientific approach to the formation of a dynamic functional structure of professional activity, whose psychological basis in its dialectical unity is the profound knowledge and high level of the general culture of the individual, high moral qualities, high cognitive activity and independence, abilities and professional skills, interest in activities. Human activity is an objective process of interaction between a social environment and a person. Due to conscious activity, a person enters into various interactions with other people, forms their own attitude towards their activities, their own intentions and aspirations. Mental processes and human properties do not arise independently and isolated from each other: they are closely interconnected in a single act of a socially determined conscious activity of the individual, therefore, the effectiveness of the activity depends on the general development of the individual and, above all, on the direction of his mind, feelings and will. The essence of professional activity is the unity of emotional-sensory and intellectual development, the education of the true person.

Діяльність людини – це об'єктивний процес взаємодії суспільного середовища та людини. Завдяки свідомій діяльності, людина вступає в різноманітні взаємодії з іншими людьми, формує власне ставлення до їх діяльності, власні наміри та прагнення. Психічні процеси і властивості людини не виникають самостійно та ізольовано один від одного: вони тісно взаємопов'язані в єдиному акті суспільно обумовленої свідомої діяльності особистості, тому ефективність діяльності залежить від загального розвитку особистості та передусім від спрямованості її розуму, почуттів і волі.